Existence of Presidential Regulation in the Legislative Regulation System - Husen, Ahmad (Lex Scientia Law Review, 2019)
Presidential Regulations are Legislations made by the President. Prior to the enactment of Law Number 10 of 2004 Juncto Law Number 12 of 2011, the term Presidential Regulation was unknown. The term used is Presidential Decree. This research is a normative research. The form of this research is prescriptive research, namely research aimed at getting suggestions about what to do to solve problems. The research approach used includes a statutory approach and a case approach. The type of data used is secondary data. The analysis used in this research is descriptive qualitative. The results of this study are that after the enactment of the law, it is not appropriate to replace the term Presidential Decree with Presidential Regulation.